Transnationalising reactionary conservative activism: A multimodal critical discourse analysis of far-right narratives online. Issue 2 (3rd April 2022) - Zhang, Xinyi; Davis, Mark
ABSTRACT: By conducting a qualitative content analysis of 400 far-right posts collected from two UK-based websites – British First and Politicalite, and two Australia-based websites – The Unshackled and XYZ, this article identifies their transnational correspondences in terms of thematic focuses, philosophical foundations, and racial frames. It discusses not only topical issues and events that drive transnational far-right activism, but also its philosophical traditions – from Maurice Barrès' fin-de-siècle nationalism to Alain de Benoist's Nouvelle Droite (ND – New Right) thinking and birth-cultural nationalism – and its use of racial frames, such as white guilt, 'anti-white' racism and 'white genocide'. A multimodal critical discourse analysis of selected posts further adds to an understanding of a reactionary backlash against the perceived dominance of liberalism and 'political correctness' in contemporary Western democracies.